Scs system links copper and redox homeostasis in bacterial pathogens - Mendez, Andrea Analia Elena (2024)
The bacterial envelope is an essential compartment involved in metabolism and metabolites transport, virulence and stress defense. Its roles become more evident when homeostasis is challenged during host-pathogen interactions. In particular, the presence of free radical groups and excess copper in the periplasm causes noxious reactions, such as sulfhydryl group oxidation leading to enzymatic inactivation and protein denaturation. In response to this, canonical and accessory oxidoreductase systems are induced, performing quality control of thiol groups, and therefore contributing to restore homeostasis and preserve survival under these conditions. Here, we examine recent advances in the characterization of the Dsb-like, Salmonella-specific Scs system. This system includes the ScsC/ScsB pair of Cu+-binding proteins with thiol-oxidoreductase activity, an alternative ScsB-partner, the membrane-linked ScsD, and a likely associated protein, ScsA, with a role in peroxide resistance. We discuss the acquisition of the scsABCD locus and its integration into a global regulatory pathway directing envelope response to Cu stress during the evolution of pathogens that also harbor the canonical Dsb systems. The evidence suggests that the canonical Dsb systems cannot satisfy the extra demands that the host-pathogen interface imposes to preserve functional thiol groups. This resulted in the acquisition of the Scs system by Salmonella. We propose that the ScsABCD complex evolved to connect Cu and redox stress responses in this pathogen as well as in other bacterial pathogens.